2000
DOI: 10.1007/s004670000480
|View full text |Cite
|
Sign up to set email alerts
|

Calcium channel blockers: pharmacology and place in therapy of pediatric hypertension

Abstract: The calcium channel blockers (CCBs) are a diverse group of antihypertensive medications with variable pharmacokinetics and clinical effects. Although CCBs have been widely applied to the treatment of hypertensive children, data regarding the pharmacokinetics, efficacy and safety of these agents in children are extremely limited. In this review we briefly summarize the mechanism of action of CCBs and then summarize pertinent pharmacokinetic information on each of the CCBs commonly used in children, including am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
104
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(110 citation statements)
references
References 126 publications
(180 reference statements)
2
104
0
4
Order By: Relevance
“…The adverse effects of calcium channel blockers are generally minor and include peripheral edema and headache. These are due to the peripheral vasodilation caused by these agents [35,36]. If a primary care physician is uncertain how to proceed with hypertension workup, but needs to start therapy (e.g.…”
Section: Indications and Contraindicationsmentioning
confidence: 99%
See 4 more Smart Citations
“…The adverse effects of calcium channel blockers are generally minor and include peripheral edema and headache. These are due to the peripheral vasodilation caused by these agents [35,36]. If a primary care physician is uncertain how to proceed with hypertension workup, but needs to start therapy (e.g.…”
Section: Indications and Contraindicationsmentioning
confidence: 99%
“…Amlodipine is dosed once daily; full effect is commonly not seen until the after steady state is reached, often after 5-6 days of therapy, due to its long half-life of 36-45 hours [36]. A multicenter pharmacokinetics study showed that weight-adjusted clearances and volume of distribution were significantly greater in younger children, suggesting a need for higher amlodipine mg/kg/day doses in children less than 6 years of age [37].…”
Section: Relevant Within Class Differencesmentioning
confidence: 99%
See 3 more Smart Citations